Edukasi Pijat Oksitosin untuk Meningkatkan Produksi ASI pada Ibu Menyusui - Suhita Tri Oklaini; Waytherlis Apriani; Dewi Aprilia Ningsih I; Rifda Neni; Hanifa Hanifa (CV. ALIM'SPUBLISHING, 2026)
The low coverage of exclusive breastfeeding is still a public health challenge because it has a direct impact on infant health. Factors that cause low coverage of breastfeeding include problems in the breastfeeding process, economic conditions, environmental support, and socio-cultural aspects. Milk production is influenced by the hormone prolactin, while milk production is influenced by the hormone oxytocin. One of the interventions that has been proven to help with breast milk production is oxytocin massage. Based on this, this community service activity was carried out as an effort to increase breast milk production in breastfeeding mothers. The method of the activity is in the form of health counseling to pregnant women in the third trimester with educational media in the form of presentation materials. The activity was complemented by discussions, questions and answers, and demonstrations of the right oxytocin massage techniques to strengthen participants' understanding. The implementation of the activity went well and received enthusiasm from the participants. The results of the activity showed an increase in pregnant women's knowledge about the importance of exclusive breastfeeding and skills in performing oxytocin massage. Thus, this activity is expected to support the increase in exclusive breastfeeding coverage through the empowerment of pregnant and lactating women, as well as a promotive-preventive strategy in maintaining the health of babies in a sustainable manner.